Wide area measurement system in the IEEE-14 bus system using multiobjective shortest path algorithm for fault analysis - Awalin, Lilik J.; Syahirah, Abd Halim; Jafferi, Jamaludin; Nor Azuana, Ramli (Science and Information Organization, 2021)
In a large-scale interconnected power system network, few challenges exist in evaluating and maintaining the overall system stability. The power system's ability to supply all types of loads during natural disasters or faults has yet to be addressed. This work focuses on developing a wide-area measurement system to manage and control the power system under all operating conditions. The IEEE-14 bus system was modeled in PSCAD software for simulating nineteen types of fault based on multi-objective shortest path algorithm. To manage the wide area measurement, the research must comprehend the working principle of the multi-objective shortest path algorithm, whereby the proposed method will determine the new path for the IEEE-14 bus system. To evaluate the performance of the multi-objective shortest path algorithm, all sections of the IEEE-14 bus system were simulated with faults. The distances of the normal path (without simulated fault) and the new path (with simulated fault) were recorded. Based on the recorded data, it was found that the location of the fault has significant influence on the shortest path of the buses connected to each other.